Japan : Staff Report for the 2006 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Japan showed strong economic recovery from the crisis. Executive Directors welcomed the development and stressed the need for a strong monetary framework, well-designed fiscal consolidation, and structural reforms. Directors agreed that the Bank of Japan's monetary framework is well suited to the post deflation environment and welcomed the improvement in transparency. Directors appreciated the progress in fiscal consolidation and structural reforms. They encouraged the authorities to maintain an ambitious reform program to support balanced global growth and an orderly resolution of global current account imbalances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet